Interplanetary Origins of Some Intense Geomagnetic Storms During Solar Cycle 24 and the Responses of African Equatorial/Low‐Latitude Ionosphere to Them. Issue 2 (5th February 2021) - Arowolo, O. A.; Akala, A. O.; Oyeyemi, E. O.
Abstract: The interplanetary origins of eight selected intense geomagnetic storms that occurred during solar cycle 24 and the responses of total electron content (TEC) at eight African equatorial/low‐latitude stations to these storms were investigated. The responses of scintillations at Dakar and Addis Ababa to the 2011 and 2013 storms were also studied. Six of the eight storms were driven by interplanetary coronal mass ejection (ICME) transients: sheath fields, magnetic clouds, or both. The other two were driven by Co‐rotating interaction region (CIR). In the African equatorial/low‐latitude ionosphere, the TEC was particularly modified by the geomagnetic storms investigated. Our results showed that TEC responses to these storms' initial phases were generally negative. The ICME‐driven storms with daytime main phases caused pole‐ward transport of plasma from the magnetic equator toward the equatorial ionization anomaly (EIA) crests and equator‐ward movement of plasma from the daytime EIA crests' locations, for those with local nighttime main phases, which we attributed to the effect of prompt penetration electric field diurnal orientations. We observed that all the phases of the two CIR‐driven storms majorly recorded negative ionospheric phases. Overall, the storm‐phase‐related equatorial/low‐latitude ionospheric responses were observed to be local time‐dependent and governed by the geomagnetic storms' interplanetary drivers. Comparatively, the CIR‐driven storms investigated were less geoeffective than the ICME transients‐driven storms investigated. Key Points: Phase of ionospheric response to storms is dependent on local time of storm's unfolding and IP driver Daytime main phase ICME‐driven storms caused pole‐ward transport of plasma and equator‐ward movement of plasma for nighttime ones CIR‐driven storms are comparatively less geoeffective than ICME‐driven storms